Deacetylation of mycothiol-derived 'waste product' triggers the last biosynthetic steps of lincosamide antibiotics - Kamenik, Zdenek; Kadlcik, Stanislav; Radojevic, Bojana; Jiraskova, Petra; Kuzma, Marek; Gazak, Radek; Najmanova, Lucie; Kopecky, Jan; Janata, Jiri (Chemical science, 2016)
The immediate post-condensation steps in lincomycin biosynthesis are reminiscent of the mycothiol-dependent detoxification system of actinomycetes. This machinery provides the last proven lincomycin intermediate, a mercapturic acid derivative, which formally represents the 'waste product' of the detoxification process. We identified and purified new lincomycin intermediates from the culture broth of deletion mutant strains of Streptomyces lincolnensis and tested these compounds as substrates for proteins putatively involved in lincomycin biosynthesis. The results, based on LC-MS, in-source collision-induced dissociation mass spectrometry and NMR analysis, revealed the final steps of lincomycin biosynthesis, i.e. conversion of the mercapturic acid derivative to lincomycin. Most importantly, we show that deacetylation of the N'-acetyl-S-cysteine residue of the mercapturic acid derivative is required to 'escape' the detoxification-like system and proceed towards completion of the biosynthetic pathway. Additionally, our results, supported by l-cysteine-13C3, 15N incorporation experiments, give evidence that a different type of reaction catalysed by the homologous pair of pyridoxal-5'-phosphate-dependent enzymes, LmbF and CcbF, forms the branch point in the biosynthesis of lincomycin and celesticetin, two related lincosamides.